2020
DOI: 10.29252/jmp.1.73.143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodae herbal capsule on migraine headaches

Abstract: Background: Migraine is a common neurobiological disorder and various methods have been proposed for its treatment, including herbal remedies. Sodae is an herbal capsule produced and marketed by "Booali Daroo" Pharmaceutical Company, based on Iran's traditional medicine, in compliance with the instructions of the Food and Drug Administration of Iran and with a license issued by this administration of the Ministry of Health. Objective: The present study was conducted to compare the effects of Sodae and placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…37 Mansour Rezaei investigated the effect of Sodae herbal capsule, a product contains Terminalia chebula, Turpethum, Bdellium, Rhubarb, and Eyaraj fighara, for the treatment of migraine, and the study results confirmed the effectiveness of these plants in reducing the frequency of migraine attacks. 38 Saussurea lappa has been shown an anti-migraine effect and it decreases calcium, magnesium, serotonin in serum and increases phosphorus, and alkaline phosphatase concentrations in serum. 39 According to Arman Zargaran's study, apigenin showed the anti-migraine effect.…”
Section: Discussionmentioning
confidence: 99%
“…37 Mansour Rezaei investigated the effect of Sodae herbal capsule, a product contains Terminalia chebula, Turpethum, Bdellium, Rhubarb, and Eyaraj fighara, for the treatment of migraine, and the study results confirmed the effectiveness of these plants in reducing the frequency of migraine attacks. 38 Saussurea lappa has been shown an anti-migraine effect and it decreases calcium, magnesium, serotonin in serum and increases phosphorus, and alkaline phosphatase concentrations in serum. 39 According to Arman Zargaran's study, apigenin showed the anti-migraine effect.…”
Section: Discussionmentioning
confidence: 99%